Fenomena childfree dalam perspektif maqashid syariah dan maslahah mursalah - Maula, Muhammad Jad (Maliki Interdisciplinary Journal, 2024)
Childfree has become a world phenomenon today. Its existence continues to give rise to problems among society. Childfree in Indonesia is starting to become known through trends that come from the Western world. Recently, the term childfree has become hot again among the public, especially teenagers, because one influencer openly stated that he is one of those who follow childfree. The spread of this term occurred significantly because it was through public figures. Many discussions about childfree have been found on internet pages. Through the Islamic paradigm, the childfree phenomenon has received a lot of criticism and harsh comments. This is because childfree is generally contrary to maqashid sharia. With the majority of the population being Muslim, there is a need for writing that can help people understand childfree within the Islamic paradigm. Therefore, writing about childfree through the Islamic paradigm needs to be presented in a straightforward and comprehensive manner. This article aims to educate the public, especially Muslims, about childfree law and its position in the welfare of society. A review of childfree seen from its benefits will give rise to clear laws using the legal istinbath of maslahah murlah. These results can be embraced by society at large so that they are no longer on the verge of confusion.